Probing the mechanism of H2 production in water gas shift reaction over Ce-modified CaO: A DFT study. (April 2022) - Yan, Xianyao; Li, Yingjie; Sun, Chaoying; Chu, Leizhe; Yang, Liguo; Fan, Xiaoxu
Abstract: The sorption-enhanced water gas shift reaction (WGSR) using CaO-based materials is a promising technology for H2 production, which can be further improved with the Ce-modified CaO material. However, the underlying mechanism for WGSR with the assistance of Ce-modified CaO remains unclear. A Ce-modified CaO periodic slab model was established in this paper, and the density functional theory (DFT) simulations for WGSR characteristics on Ce-modified CaO surface were performed. The results demonstrate that the Ce-modified CaO exhibits higher electron density, and the electron transfer between Ce and adjacent O is observed. The Ce doping obliterates the band gap of CaO, and the Fermi level is penetrated by O 2p orbit of Ce-modified CaO. The intermediates involved in WGSR exhibit obvious mutual promotion for co-adsorption with Ce-modification, and the H2 desorption is facilitated by the absorbed CO2 . Ce doping avoids the generation of an additional intermediate, and the energy barriers of H2 generation and CO2 adsorption are reduced. The rate-limiting step on Ce-modified CaO is altered to the cleavage of O–H bond and formation of CO2 radical, and the energy barrier is 2.15 eV, which is 34.6% lower than that on CaO. Therefore, the enhancement mechanism on H2 production in WGSR resulted by Ce-modified CaO was determined. Highlights: WGSR mechanism on Ce-modified CaO along redox pathway was studied by DFT calculation. Interaction of Ce and O is higher than that of Ca and O. Fermi level is penetrated by O 2p orbit in Ce-modifed CaO. Ce inhibits CO + O+2H generation and reduces numbers of intermediates in WGSR. Energy barriers of CO2 generation and adsorption are reduced on Ce-modified CaO.